Regaining control over alcohol intake but not abstinence on disulfiram medication, as a harm reduction approach: 2 case reports - Max Schallenberg; Maximilian Pilhatsch; Johannes Petzold; Diana Vogel-Blaschka; Ulrich S. Zimmermann; Maik Spreer (Addiction Science & Clinical Practice)
Abstract Background Alcohol use disorder (AUD) poses severe health risks, yet many affected individuals opt out of complete abstinence. Therefore, harm reduction strategies have become more prominent in treatment guidelines for AUD. Our two case reports illustrate how disulfiram, initially intended to enforce abstinence, was repurposed to support reduced drinking. Case Presentations A 41-year-old patient with a history of severe AUD successfully reduced his alcohol consumption to a low-risk level by leveraging the effects of the disulfiram-alcohol aversive reaction. Another patient, a 63-year-old woman with long histories of AUD and major depressive disorder, experienced fewer depressive episodes and hospitalizations with disulfiram therapy despite periodically intentional discontinuation of medication. Conclusion Individualized treatment strategies are critical in optimizing outcomes for patients with AUD. Continuous disulfiram therapy, despite its limitations in directly reducing alcohol intake, might offer a new avenue for harm reduction in exceptional cases even if alcohol consumption continues. The cases suggest that maintaining therapy, aiming at reduced drinking, can enhance the therapeutic alliance and help manage comorbid conditions. Regular medical monitoring is essential for safety and efficacy, warranting further study of possible long-term consequences and psychotropic effects of elevated acetaldehyde levels related to the disulfiram-alcohol interaction.